Human rights and constitution making - United Nations Human Rights Office of The High Commissioner; United Nations. High Commissioner for Human Rights; United Nations. Office of the High Commissioner for Human Rights; United Nations (New York ; Geneva : United Nations Human Rights Office of the High Commissioner, 2018)
This publication is designed to assist United Nations staff who provide human rights advice to States, which undertake to amend an existing constitution or write a new one. It should also be of use to States that undertake constitutional reform, including political leaders, policymakers, legislators and those entrusted to draft constitutional amendments or a new constitution. Further this publication should also facilitate advocacy efforts by civil society to ensure that human rights are properly reflected in constitutional amendments or new constitutions. Finally, this publication, along with the international human rights instruments, should not only provide a standard to measure whether constitutional amendments or a new constitution has appropriately reflected human rights and fundamental freedoms, but also assist in evaluating whether the processes used in constitutional reform are consistent with international procedural norms'--Introduction, page 1.
Part 1. Constitutional reforms and human rights. Why a rights-based approach to constitutional reform? ; Human rights and the process of constitutional reform -- Part 2. Constitutional bill of rights. The constitutional bill of rights and international human rights standards ; Drafting a constitutional bill of rights : general requirements ; Content of the constitutional bill of rights ; Institutional and procedural guarantees of rights -- Part 3. OHCHR and human rights mechanisms. Contribution of human rights mechanisms ; Objectives, forms and methodology of assistance programmes ; Partnerships.
Includes bibliographical references (pages 139-144).
Keywords: Constitutional law; Human rights; Civil rights; Law reform